The application of artificial technology in pediatric pyeloplasty the efficacy analysis of robotic-assisted laparoscopic pyeloplasty in the treatment of ureteropelvic junction obstruction - Hu, Zhongli; Chen, Shan; Wang, Zhihong; Xu, Di; Zhang, Xiaolang; Lin, Yang; Zhang, Lin; Wang, Jianbin; Li, Lizhi (Frontiers in Pediatrics, 2023)
Objective To investigate the clinical effect of the da Vinci robotic-assisted laparoscopic pyeloureteroplasty (RALP) in treating pediatric ureteropelvic junction obstruction (UPJO). Methods We retrospectively analyzed clinical data from 32 children with UPJO who suffered from RALP in our hospital from October 2020 to February 2023, compared with those treated with common laparoscopy at the same time. After the establishment of the robotic arm, a mesenteric approach was performed after entering the abdominal cavity to focus on the lesion site. The dilated renal pelvis was then cut and the stenotic ureter was removed; the anastomosis and the incision were sutured by layer. Results A total of 62 children (44 boys and 20 girls) with a median age of 14 months (ranging from 3 to 38 months) were included. All 62 cases had hydronephrosis caused by unilateral UPJO, and the surgery was successfully completed without conversion to open. All intraoperative blood losses amounted to less than 10 ml. In the RALP group, the average operative duration was 131.28 min (ranging from 108 to 180 min). The average catheter time was 3.66 days (ranging from 2 to 7 days). The average hematuria time was 3.84 days (ranging from 2 to 6 days). The average postoperative hospital stay was 7.8 days (ranging from 6 to 12 days). The average hospitalization costs were 59,048.31 yuan (ranging from 50,484 to 69,977 yuan). The double-J tube was removed 1 month after surgery. Only one patient suffered from complications, developing a urinary tract infection 4 weeks after surgery, and was cured with the administration of oral cefaclor anti-inflammatory drugs for 3 days. All patients were followed up for 2–28 months, with a median follow-up time of 12 months. The thickness of the renal cortex was increased after surgery [(1.95 ± 0.24) vs. (4.82 ± 0.50)] cm, and the isotope renograms revealed a definite recovery of the split renal function [(28.32 ± 1.95) vs. (37.01 ± 2.71)]%. Conclusion The robotic-assisted laparoscopic pyeloureteroplasty (RALP) in the treatment of children with upper ureteral obstruction has overall clinical efficiency. With technological advancements and an increased number of experienced surgeons, robotic surgery may become a new trend in surgery.